DAYA TARIK PROFESI AUDIT PADA GENERASI Z - Santoso, Stefanie Kristiana; Nainggolan, Tiurma; Tjun Tjun, Lauw; Marpaung, Elyzabet Indrawati (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
The purpose of this study is to determine the interest of Generation Z students in the auditing profession. A quantitative approach was conducted using a survey method through the distribution of a questionnaire based on Google Forms to undergraduate and postgraduate accounting students at universities in the city of Bandung. The study applied purposive sampling and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial rewards, motivation, and self-efficacy have a positive influence on students' interest in pursuing an audit profession. These findings provide insights into the factors that may impact Generation Z students' career choices regarding the audit profession in the future. Penelitian ini bertujuan untuk mengetahui minat mahasiswa generasi Z terhadap profesi audit. Pendekatan yang dilakukan melalui metode survei dengan penyebaran kuisioner berbasis google form kepada mahasiswa bidang akuntansi pada Universitas di Kota Bandung. Metode purposive sampling digunakan dalam pengambilan data, kemudian dianalisa menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil penelitian menunjukkan penghargaan keuangan, motivasi, dan efikasi diri positif berpengaruh terhadap minat mahasiswa dalam memilih profesi audit. Temuan ini memberikan wawasan tentang faktor-faktor yang dapat mempengaruhi keputusan karir mahasiswa generasi Z dalam memilih profesi audit di masa depan.